2002
DOI: 10.1097/00024720-200210000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Analysis of Lateral Vertebral Radiographic Variables and Medical Outcomes Study Short-Form Health Survey

Abstract: This prospective comparative study was designed to investigate the possible link between SF-36 functional status and lateral roentgenographic variables of the standing lumbar spine in patients with low back pain (LBP) versus asymptomatic volunteers. To the authors' knowledge, no previous studies have correlated SF-36 scores and sagittal roentgenographic variables in patients with LBP versus asymptomatic individuals. A total of 100 male volunteers, used as controls, and an equal number of age-, height-, and wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 34 publications
2
33
0
1
Order By: Relevance
“…PT, and that SS cannot be a negative number, you can tilt more with a high PI than with a low PI, since there is a much wider range through which adaptation can occur. Numerous studies reported that patients with chronic low back pain and lumbar degenerative disease were characterized by decrease of sacral slope and increase of pelvis tilt [2,8,12] as demonstrated in our illustrated case in Fig. 4.…”
Section: Pelvis Areamentioning
confidence: 56%
See 1 more Smart Citation
“…PT, and that SS cannot be a negative number, you can tilt more with a high PI than with a low PI, since there is a much wider range through which adaptation can occur. Numerous studies reported that patients with chronic low back pain and lumbar degenerative disease were characterized by decrease of sacral slope and increase of pelvis tilt [2,8,12] as demonstrated in our illustrated case in Fig. 4.…”
Section: Pelvis Areamentioning
confidence: 56%
“…5). Previous studies demonstrated that low back pain subjects were characterized by less distal lordosis, a more vertical sacrum and more proximal lumbar lordosis [8,12]. More proximal lumbar lordosis signified more extension in the upper lumbar spine.…”
Section: Hyperextension Of Adjacent Segmentsmentioning
confidence: 97%
“…Previous studies have also assessed spino-pelvic alignment in LBP and lumbar disk disease [7][8][9][10][11][12][13][14][15][16][17], but the relationship between sagittal alignment and LBP is still poorly understood. The current paper helps to better understand the relationship between sagittal alignment and LBP because it involves the largest database published so far in the literature on the evaluation of sagittal spino-pelvic alignment in chronic LBP.…”
Section: Discussionmentioning
confidence: 99%
“…Rajnics et al [11] also observed significant differences for SS, PT, and LLbut not PI nor TK-in 50 patients presenting with low back pain and disk herniation compared to 30 healthy subjects. Other studies also reported conflicting results suggesting either decreased [12], increased [13], or normal [14][15][16][17] LL in patients with LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies support the concept that the analysis of sagittal alignment of the spine is of fundamental importance in the diagnosis and therapy of degenerative diseases of the lumbar spine, especially when there is indication for surgical treatment, with instrumentation and fusion procedures included [1][2][3][4][5][6][7] . Several studies demonstrate the relationship between measurements of spinal and pelvic alignment in groups of normal subjects [8][9][10][11] and in groups of patients with lumbar degenerative disease 5,12 , with statistically significant results, but still not clinically significant i.e., with heterogeneous clinical presentations [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%